Modulating the Tumor Microenvironment via Oncolytic Viruses and CSF-1R Inhibition Synergistically Enhances Anti-PD-1 Immunotherapy - Shi, Gang (Mol Ther, 2019)
Immunotherapy based on the immune checkpoint blockade has emerged as the most promising approach for cancer therapy. However, the proportion of colorectal cancer patients who benefit from immunotherapy is small due to the immunosuppressive tumor microenvironment. Hence, combination immunotherapy is an ideal strategy to overcome this limitation. In this study, we developed a novel combination of CSF-1R (colony-stimulating factor 1 receptor) inhibitor (PLX3397), oncolytic viruses, and anti-PD-1 antibody. Our results demonstrated that the triple treatment synergistically conferred significant tumor control and prolonged the survival of mouse models of colon cancer. Approximately 43% and 82% of mice bearing the CT26 and MC38 tumor, respectively, survived long term following the triple treatment. This combination therapy reprogrammed the immunosuppressive tumor microenvironment toward a CD8(+) T cell-biased anti-tumor immunity by increasing T cell infiltration in the tumor and augmenting anti-tumor CD8(+) T cell function. Our results provide a robust strategy for clinical combination therapy.